Nadin Amizah’s Content Strategy for the “BLP Beauty” Beauty Brand on Instagram - Putri Diyah Dwi Ayu; Dedet Erawati (PT FORMOSA CENDEKIA GLOBAL, 2026)
This research was carried out qualitatively with a descriptive case study method. Observations of collaborative content on Instagram @blpbeauty and semi-structured interviews with representatives from the BLP Beauty as well as three Instagram active audiences @blpbeauty used to obtain research data. The results of the study show that this collaboration focuses on narrative building, conveying the values of self-empowerment and self-acceptance, and creating emotional closeness through consistent stories and visualizations, as well as product promotion. As a result of the cognitive, emotional, and positive behavioral engagement of the audience, BLP Beauty is considered an authentic, relevant, and valuable local brand. This study suggests that local beauty brands can implement collaborative content strategies in a planned and relevant way for their target audience to develop sustainable customer engagement.